The Relationship Between Dielectric Properties, Thermoacoustic Signals and Temperature of Liver Tissues at 3.0 GHz - Li, Jiawu; Huang, Lin; Peng, Yitong; Li, En; Luo, Yan (Frontiers in Physics, 2022)
Purpose: This study aimed to investigate the relationship between dielectric properties (permittivity and conductivity), thermoacoustic signals (TAS) and the temperature of liver tissue at 3.0 GHz. Materials and methods: An open-ended coaxial probe was used to measure the dielectric properties of fresh porcine liver tissues in vitro, and a thermoacoustic imaging (TAI) system was used to collect the TAS. Porcine liver tissues were placed on a heating platform, and the dielectric properties measuring probe and temperature sensor were inserted into liver tissues at an interval of 1.5 cm. First, liver tissues were gradually heated by a heating platform from room temperature (30 ℃) to 60 ℃, and the dielectric properties and TAS were measured when the temperature increased approximately every 1 ℃. Second, after the temperature of the porcine liver tissue reached 60 ℃, the heating platform was turned off to naturally cool the porcine liver tissue to room temperature. During the process, the dielectric properties and TAS were also measured when the temperature decreased every 1 ℃. Finally, the dielectric properties and TAS changes of liver tissues with temperature at 3.0 GHz frequency were analyzed. Results: During the process of heating tissues up to 60 ℃, the conductivity of the porcine liver tissues decreased, while the permittivity and TAS of the porcine liver tissues increased, and the relationships were nonlinearly correlated. Meanwhile, during the cooling process, the conductivity of porcine liver tissues increased, while the permittivity and TAS decreased, and the relationships were also nonlinearly correlated. Conclusions: The dielectric properties and TAS of porcine liver tissue changed significantly with temperature, which makes it possible to differentiate the safety margin during liver thermal ablation with thermoacoustic imaging (TAI). While the relationship between temperature, dielectric properties and TAS needs to be further investigated, TAI has the potential to be utilized for margin screening during thermal ablation.